Cortical Bone Derived Stem Cells Modulate Cardiac Fibroblast Response via miR-18a in the Heart After Injury - Kraus, Lindsay; Ma, Lena; Yang, Yijun; Nguyen, Faustina; Hoy, Robert C.; Okuno, Tomoko; Khan, Mohsin; Mohsin, Sadia (Frontiers in Cell and Developmental Biology, 2020)
The adult heart following injury such as a myocardial infarction forms a fibrotic scar associated with transformation of resident cardiac fibroblasts into myofibroblast, accelerating cardiac remodeling and dysfunction. Cell therapies provide a novel direction for the enhancement of cardiac structure and function but remain poorly described in terms of the effect on resident cardiac fibroblasts. We have shown cortical bone derived stem cells (CBSCs) exhibit an ability to repair the heart after myocardial injury together with reduced scar formation. Nevertheless, whether CBSCs possess ability to modulate resident fibroblast response after myocardial injury remains untested. Objective; To determine the effect of secreted factors from CSBCs to attenuate myofibroblast formation in the heart after injury. Methods and Results; CBSCs were injected in mice after myocardial infarction which demonstrated reduced fibrosis as determined by Masson’s trichrome and Picro-Sirius red staining. In parallel, decreased expression of myofibroblast markers such as Acta2 was observed compared to PBS injected mice. To determine the effect of CBSCs on cardiac fibrosis, adult mouse cardiac fibroblasts were isolated from C57BL/6 mice, primed with CBSC pre-conditioned media for 12 hours, and treated with 10ng TGF-β for 48 hours to mimic cardiac injury. Decreased expression of Acta2, periostin and CTGF was observed in adult cardiac fibroblasts cultured in CBSC medium compared to control cells. Additionally, analysis of myofibroblast markers such as vimentin and pSMAD/SMAD was also decreased compared to control cells. To determine the mechanism, we looked for enriched miRNA in CBSCs that can mediate anti fibrotic response after injury. Results showed significantly increased expression of miR-18a in CBSCs. The upregulation of miR-18a was also validated in adult fibroblasts treated with CBSCs compared to control cells. Adult fibroblasts treated with mimic for miR-18a followed by TGF-β showed significant decrease in myofibroblast formation while miR-18a inhibitor completely inhibited the effect of CBSC medium. Conclusion; CBSCs reduce fibroblast to myofibroblast transition and differentiation in adult cardiac fibroblasts via miR-18a-5p. This finding reveals a new avenue for cell therapies to target myocardial scar modulation and provides a resolution for the cardiac repair response after injury in the adult myocardium.